Socioeconomic Analysis and Technical Efficiency among Smallholder Sorghum Farmers in GaMasemola Township of Limpopo Province, South Africa - Moswane Precious Botiabane; L. Zhou; I. B. Oluwatayo; Fakunle Olufemi Oyedokun; Akeem Adewale Oyelana (Journal of Economics and Behavioral Studies, 2018)
Sorghum farming group in South Africa is divided into the smallholder and business ranchers attributable to the distinctions in cultivar sizes, utility creation and production strategies. Sorghum is utilized primarily for sustenance and refreshments in Ga-Masemola (GM) town. Smallholder sorghum farmers in the town utilize some portion of their wage for recreation, goat and cows' compost are utilized as manures to enhance soil fruitfulness and increment sorghum yield, they rely upon precipitation water for the water system and they have no entrance to expansion administrations. The study distinguish and depict the socioeconomic characteristics of smallholder sorghum farmers in Ga-Masemola town; it looks at the causes of technical efficiency among smallholder sorghum ranchers in the town, and it recognizes and portrays difficulties confronted by smallholder sorghum farmers in the town. Essential information was gathered utilizing organized surveys and an example size of 48 smallholder sorghum farmers in the town was chosen. Cobb Douglas model was utilized to analyze the information or data gotten.The socioeconomic characteristics of smallholder sorghum farmers were:farming experience, age, sexual orientation, instructive level and family unit measure. The study indicates that the determinants of technical efficiency among smallholder sorghum farmers in Ga-Masemola town that were observed to be huge are the measure of land dedicated and the amount of seeds utilized. Farmers are confronting difficulties, for example, sicknesses, low capital, pests, separation to the homestead, absence of water and atmosphere (i.e. climate) changes.The study suggested and recommended that smallholder sorghum farmers in Ga-Masemola (GM) town require arable land to expand their production; they additionally require agriculture extension officers for training and spreading or disseminating information about inputs allocation. Besides, the smallholder farmers should be encouraged to utilize enhanced seeds varieties in order to expand their technical efficiency.